Influence of irrigation systems on the plant growth and leaf ratio analyses of rubber (Hevea brasiliensis) seedlings - Nabayi, Abba; Boon, Christopher Sung Teh; Sulaiman, Zulkefly (Universiti Putra Malaysia, 2022)
The sprinkler irrigation system is the most widely used system for rubber irrigation in a nursery. However, the method is associated with high water loss during irrigation. In view of this, an experiment was conducted to assess the effect of different irrigation systems on the growth dynamics, leaf ratio analyses, water productivity, and water use efficiency of rubber seedlings. The treatments were the irrigation systems; soil + overhead sprinkler (CON), growing media (GM) + drip irrigation (DRP), GM + capillary wick system (WCK), and GM + overhead sprinkler (SPR). Each treatment was replicated three times, and the experiment was laid out in a randomized complete block design. The results showed that the DRP and WCK had significantly (p<0.05) higher seedlings’ growth parameters by 15–39% than obtained in the SPR and CON. However, the DRP, WCK, and SPR had statistically comparable seedlings’ root length and volume by 14–43% higher relative to the CON. Similar trends of plant growth dynamics, such as crop growth rate (CGR), leaf area index (LAI), and leaf ratio analyses, were observed for all treatments. However, the CON had lower CGR and LAI, which could be attributed to the lower water retention of the soil used in the treatment. The DRP and WCK had comparable water productivity with 56–60% higher than the SPR and CON treatments. The sprinkler irrigation treatments (SPR and CON) had 84% lower water use efficiency than the DRP and WCK. The DRP and WCK are the best treatments in this study because their higher water application uniformity led to higher seedlings’ growth dynamics and water productivity. The sprinkler system had higher water loss due to the lack of application uniformity, leading to lower plant growth than other irrigations. However, the SPR shows the potential to be more cost-effective due to its lower recurrent cost of labor than drip and wick irrigation.